Overlapping Authorities of the BPK and BPKP and Their Implications for Contractors - Zuvika Alfi Aulia (Universitas Cokroaminoto Yogyakarta, 2026)
The construction services sector holds a strategic position in Indonesia’s national development. Nevertheless, the practical execution of government construction projects often encounters legal issues, including ambiguous contracts, unilateral design changes without addenda, and delays in payment. In the sphere of state financial oversight, two key institutions perform crucial functions: Badan Pengawasan Keuangan dan Pembangunan (BPKP) and Badan Pemeriksa Keuangan (BPK) as the external auditor. Both bodies possess the legal authority to audit construction projects and assess potential state financial losses. However, overlapping authority in determining losses and issuing recommendations frequently occurs. This study employs normative legal and sociological approaches to analyze the respective roles and mandates of BPKP and BPK, as well as the implications of dual audit authority for contractors’ legal certainty. Data were gathered through literature review, regulatory analysis, and examination of audit findings. The results demonstrate that dual authority contributes to legal uncertainty, particularly concerning the valuation of state losses and follow-up actions arising from audit reports. Furthermore, contractors are often confronted with conflicting findings that create inefficiency, confusion, and heightened legal risk. The study suggests the need for regulatory harmonization and improved coordination mechanisms between audit institutions to enhance transparency, accountability, and legal certainty in construction project implementation.